Metodologias ativas e a elaboração de modelos anatômicos no ambiente educacional: para facilitar o ensino e aprendizado de ciências no ensino fundamental - Costa, Albanísia Teixeira da (2024)
In this study, we carried out a scientific investigation focused on the morphological aspects of the circulatory system, with the aim of promoting integrated, meaningful, and active learning in the context of science teaching. The main objective of the research is to analyze the dynamics of teaching and learning Anatomy in a municipal public school in Fortaleza. This was done through the application of active methodologies associated with practice using an anatomical part of the pig heart as active approaches during science lessons. In addition, we investigated the students' perception of the methodologies used. To achieve this, we conducted a quasiexperimental study, using a mixed methods approach combining qualitative and quantitative methods. We focused on describing and exploring the elements in question, dividing the process into four stages. The first stage involved the application of questionnaires and the use of the Plickers platform with a peer learning methodology. In the second stage, we held a didactic workshop. The third stage consisted of software a word cloud with the Wordle platform, while the fourth stage involved the statistical analysis of the data collected in stage 1. The data analysis included a percentage analysis and statistical tests, such as the Shapiro-Wilk test and Wilcoxon post-test, using the GraphPad Prism program version 8.0. Data with a p-value of <0.05 was considered significant, confirming the effectiveness of the methodological steps used to teach science. This process resulted in an enriching, interdisciplinary, inclusive, playful, and meaningful experience for final-year elementary school students. In summary, this research highlighted the originality of the approach adopted to promote teaching and learning in science, integrating anatomical aspects and active methodologies through theoretical and practical exposure to components of the human cardiovascular system.